Religion and popular culture : rescripting the sacred - Santana, Richard W.; Erickson, Gregory (Jefferson, N.C. : McFarland, 2008)
"This work considers ways in which American cultural products such as TV, advertising, music, and video games have played a significant role in creating, representing, and influencing contradictory religious identities"--Provided by publisher.
Popular culture and popular religion in America -- "Jesus is standing at home plate" : baseball and American Christianity -- Consuming faith : advertising, the pornographic gaze and religious desire -- Absolute contradictions : perceptions of the spiritual and the religious in popular music -- The gods of film : representing God and Jesus at the movies -- Television drama, fan communities and theology : God as "nothing solid" -- Demons, aliens and spiritual warfare : belief and reality -- Evil reloaded : political rhetoric, philosophy, and video games after 9/11.
Includes bibliographical references (p. 211-219) and index.
Keywords: Religion and culture -- United States; Popular culture -- Religious aspects; United States -- Religion